Analysis of Maslahah Mursalah Comparison of the Settlement of Sharia Insurance Contracts at National Sharia Arbitration Board and the Indonesian Insurance Mediation and Abitration Agency - Sativa, Annisa; Ansari, Ansari; Panjaitan, Budi Sastra (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This paper aims to share knowledge and provide another point of view regarding the view of Maslahah Mursalah Analysis of Comparative Settlement of Sharia Insurance Contracts at National Sharia Arbitration Board and the Indonesian Insurance Mediation and Abitrase Agency. Insurance is defined as a reasonable (fair) transfer of the risk of loss, from 1 (one) entity to another entity. And to guarantee and resolve insurance disputes, of course, requires an institution that is willing to take over the risks of the community, both individual risks and group risks caused. The two institutions discussed are National Sharia Arbitration Board and Indonesian Insurance Mediation and Arbitration Agency. The problems to be discussed in this research are about how the comparison of the binding force of the decision of the National Sharia Arbitration Board and the Indonesian Insurance Mediation and Arbitration Board (Indonesian Insurance Mediation and Arbitration Agency) in the Settlement of Sharia Insurance Contract Disputes, and how the dispute resolution by Indonesian Insurance Mediation and Arbitration Agency and National Sharia Arbitration Board and the Maslahah Mursalah review of the nonlitigation mediation. In this research the author uses normative legal research. The research uses literature as a reference, namely books or journals and supporting materials that discuss these two institutions. And the results of the research in this paper are the two institutions intended to resolve insurance disputes, namely National Sharia Arbitration Board and Indonesian Insurance Mediation and Arbitration Agency. Disputes are resolved by National Sharia Arbitration Board if the dispute cannot be resolved by internal deliberation by the insurance company. While disputes are resolved by Indonesian Insurance Mediation and Arbitration Agency, namely if the insured has a dispute with the insurance company and cannot reach a settlement of the dispute. The two institutions have permanent legal force.